Dekonstruksi Kegagalan Prinsip Value For Money: Analisis Ketimpangan Realisasi Pendapatan Dan Belanja Daerah - Aribah Muthi’ Choironi; Putri Rizkiyah; Alam, Arya Pamungkas Pitu; Dian, Kisma; DP, Rina Tjandra Kirana (GLOBAL SCIENTS PUBLISHER, 2026)
The imbalance between realized regional revenue and expenditure is a key indicator of the failure to implement the Value for Money (VfM) principle in regional financial governance. A systematic literature review (SLR) identified that effective revenue target achievement is often not accompanied by adequate spending efficiency. This phenomenon is caused by three systemic factors: fragmented indicator design that separates effectiveness and efficiency measurements, information asymmetry in agency mechanisms, and the dominance of administrative indicators in the Public Financial Management (PFM) system. This situation creates an